The cerebrospinal fluid virome in people with HIV: links to neuroinflammation and cognition - Trunfio, Mattia; Scutari, Rossana; Fox, Valeria; Vuaran, Elisa; Dastgheyb, Raha Maryam; Fini, Vanessa; Granaglia, Annarita; Balbo, Francesca; Tortarolo, Dora; Bonora, Stefano; Perno, Carlo Federico; Di Perri, Giovanni; et al. (Frontiers in Microbiology, 2025)
IntroductionDespite durable viral suppression, neuroinflammation and neurocognitive complications remain common yet poorly understood in people with HIV (PWH). HIV alters human viromes, and virome perturbations have been linked to neurocognitive issues in people without HIV. Recently characterized, the brain and cerebrospinal fluid (CSF) viromes represent a new avenue to understand brain and mental health in PWH.MethodsThis cross-sectional study analyzed 85 CSF samples (74 from PWH on suppressive antiretroviral therapy, and 11 from controls without HIV, CWH) through shotgun metagenomics for DNA and RNA viruses. Taxonomic composition (reads and contigs), diversity, and relative abundance (RA) of prokaryotic (PV), human eukaryotic (hEV), and non-human eukaryotic viruses (nhEV) were evaluated in relation to HIV status, markers of neuroinflammation/neurodegeneration, cognitive functions, and depressive symptoms. Sensitivity analyses and post-hoc cluster analysis on the RA of hEV, non-human viruses (NHV) and blood–brain barrier permeability were performed. Multivariable models assessed the relationship between cognition and clusters.ResultsOf 46 read-positive CSF samples, 93.5% contained PV sequences, 47.8% hEV, and 45.6% nhEV. PWH displayed lower α diversity, although p > 0.05. At β diversity analysis, HIV status explained 3.4% of the variation in viral composition (p = 0.016). Contigs assembly yielded 13 samples positive for 8 hEV, 2 nhEV, and 6 PV. Higher RA of PV was correlated with higher CSF S100β (rho 0.36, p = 0.002) and β-Amyloid 1–42 fragment (βA-42, rho 0.27, p = 0.026), whereas higher RA of nhEV with poorer cognitive performance (rho 0.26, p = 0.022). Conversely, higher RA of hEV correlated with better cognition (rho −0.38, p = 0.003) and lower βA-42 (rho −0.30, p = 0.012). Sensitivity analyses restricted to only CSF samples with detectable reads confirmed these findings. Three CSF clusters were identified and showed differences in astrocytosis, βA-42, tau protein, and cognitive functions. Participants with hEV-enriched CSF showed better cognitive performance compared to those with virus-devoid and NHV-enriched CSF (all p < 0.05).ConclusionThis study provides the first comprehensive description of the CSF virome in PWH, revealing associations with neuroinflammation and cognition. These findings highlight the potential involvement of the CSF virome in brain health and inform about its composition, origin, and potential clinical implications in people with and without HIV.